Vengeance is mine the Mountain Meadows Massacre and its aftermath - Turley, Richard E. Jr. 1956-; Brown, Barbara Jones 1968- (Oxford University Press, 2023)
"Published by Oxford University Press in 2008, Massacre at Mountain Meadows relied on new and exhaustive research to tell the story of one of the grimmest episodes in Latter-day Saint history. On September 11, 1857, southern Utah settlers slaughtered more than 100 emigrants of a California-bound wagon train. In this much-anticipated sequel, Richard E. Turley Jr. and Barbara Jones Brown follow up that volume with an examination of the aftermath of the atrocity. In greater detail than ever before, Vengeance Is Mine documents southern Utah leaders' attempts to cover up their crime by silencing witnesses and spreading lies about the victims and perpetrators of the crime. Investigations by both governmental and church bodies were stymied by stonewalling and political wrangling. While nine men were eventually indicted, five were captured and only one, John D. Lee, was executed. The book examines the maneuvering of the defense and prosecution in Lee's two trials, the second ending in Lee's conviction. The book examines the fraught relationship between Lee and church president Brigham Young, including what Young knew of the crime and when he knew it. The book also tells the story of the seventeen young children who survived the massacre and their later return to Arkansas, from where the ill-fated wagon train originated. The book traces the fate of the perpetrators to the end of their lives, including the harrowing demise of Nephi Johnson, who screamed, "Blood! Blood! Blood!" in the delirium of his death bed more than sixty years after the massacre."
Includes bibliographical references and index
Keywords: Geschichte; Strafverfolgung; Mountain-Meadows-Massaker; Prozess; Utah; Lee, John D / (John Doyle) / 1812-1877 / Trials, litigation, etc; Mountain Meadows Massacre, Utah, 1857; Massacres / Utah; Murder / Investigation / Utah; Mormons / Utah / History / 19th century